Kearifan Lokal dalam Kumpulan Puisi Kidung Cisadane Karya Rini Intama (Kajian Ekokritik Sastra) - Sulistijani, Endang (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2018)
This study aims to describe the local wisdom contained in the collection of Kidung Cisadane poem by Rini Intama. The reason for the selection of this research object because in this collection of poetry is not only presented values that are considered as the ideal reference standard of human behavior in life as a social creature, but also as an ecological creature. The method used in this research is the ecocritical method of literature with the model of environmental literature review and model of ethical studies. A study of ecological literature in eco-criticism can construct literary faces in local wisdom, while ethical perspective studies in ecocritical studies can describe the values of environmental wisdom. With the second model of the study, the ecological and cultural dimensions that have been lacking in full attention in literature can be further enhanced. In addition, in line with the development of the times, literature always voiced both cultural and ecological aspects